Medication Overuse Headache. Issue 7 (2nd July 2014) - Munksgaard, Signe B.; Jensen, Rigmor H.
<x xml:space="preserve">Abstract</x> Background Medication overuse headache (MOH) affects between 1% and 2% of the general population but is present in up to 50% of patients seen in headache centers. There are currently no internationally accepted guidelines for treatment of MOH. Methods A review of the current literature on MOH treatment and pathophysiology. Results We conclude that headache frequency can be reduced to episodic headache in more than 50% of the patients by simple detoxification and information. Approximately half the patients will not have need for prophylactic medication after withdrawal. Pain perception is altered in patients with MOH but can be restored to a baseline pattern, indicating a reversible mechanism in the central sensitization leading to chronic pain. The great comorbidity with depression and anxiety could be a consequence of the altered serotonin metabolism indicating a reversible and potentially treatable condition. Conclusion Increased focus on MOH is extremely important, as MOH both can and should be treated and prevented. MOH is thus a diagnosis that should be considered in all chronic headache patients as the very first step in their management strategy. In the general population, prevention campaigns against MOH are essential to minimize chronic pain disability.